SUSTAINABLE GREEN ECONOMIC GROWTH IN INDIA THROUGH GREEN FINANCE - Begum, Nasrin; Choudhury, Abul Khair (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green finance connects the financial sector, environmental enhancement, and economic growth is an important aspect of low-carbon green growth. The study aims to examine green finance and assess the viability of the concept in Indian business sector for mitigating ecological degradation resulting from the assimilation of carbon emissions in the atmosphere. Green finance is a market-driven financing or investment program that uses environmental incentives to influence business decisions or that incorporates environmental effect into risk assessment. The paper thus explores into current trends as well as the prospects and constraints that lie ahead for green finance in developing India. In addition to aiming to enhance social justice and human well-being, green investment also acknowledges the importance of the environment and its natural capital and attempts to mitigate environmental risks and maintain ecological integrity.